Inverse Design and Flow Distribution Analysis of Carreau Type Fluid Flow through Coat-Hanger Die - Yilmaz, Oktay; Kirkkopru, Kadir (KOREAN FIBER SOC, 2020)
An analytical/numerical method is revisited and proposed for process material specific design of coat-hanger dies. For this aim, both representative viscosity approach (RVA) and electrical network method (ENM) are employed in combination within an iterative calculation process. Under favour of RVA, any viscosity model from the family of generalized Newtonian fluid models such as that of Carreau-Yasuda can be used within broad extrusion rate range in ENM without limitation in low and high values of shear rates. This provides great flexibility and accuracy in ENM which is a relatively simple and fast numerical method. First, this method is employed to design die geometry for a specific thermoplastic melt that provides uniform flow rate at the die exit. Later, the same method is modified and used to investigate the effects of non-newtonian fluids with varying power-law indices on the die performance. Evaluation of the performance of ENM coupled with RVA (ENM-RVA) is made by computational fluid dynamics (CFD) analyses. CFD analyses indicated that the method is very successful in designing die geometry for a specific fluid. Flow distributions predicted by the method for various fluids are in accordance with those of CFD runs. The ENM-RVA is a design/analysis technique which can be employed to see effects of material rheology and throughput on the coat-hanger die performance in a short time and can be used as an auxiliary tool which can provide the preliminary design geometry for the advanced design softwares working with optimization algorithms.
Keywords: Inverse design; Representative viscosity approach; Coat-hanger die; Carreau fluid; Computational fluid dynamics; OPTIMAL GEOMETRY DESIGN; MELT FLOW; EXTRUSION; SIMULATION; VELOCITY; Materials Science; Polymer Science